2016
DOI: 10.1111/eufm.12103
|View full text |Cite
|
Sign up to set email alerts
|

Financial Hedging and Firm Performance: Evidence from Cross‐border Mergers and Acquisitions

Abstract: Using a sample of 1,369 cross‐border acquisitions announced by Standard & Poor's 1500 firms between 2000 and 2014, we find strong evidence that derivatives users experience higher announcement returns than non‐users, which translates into a US$ 193.7 million shareholder gain for an average‐sized acquirer. In addition, we find that acquirers with hedging programmes have higher deal completion probabilities, longer deal completion times, and better long‐term post‐deal performance. We confirm our findings after e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 88 publications
(113 reference statements)
0
18
0
1
Order By: Relevance
“…Existing studies have unveiled a positive relation between derivatives hedging and firm performance (see Bartram et al ., ; Haushalter et al ., ; Pérez‐González and Yun, ). More recently, Chen, Han and Zeng () also provide robust evidence in support of the view that companies who use derivative hedging achieve higher returns than non‐users do.…”
Section: Managerial Implications Of Liq‐garch Modelmentioning
confidence: 83%
See 1 more Smart Citation
“…Existing studies have unveiled a positive relation between derivatives hedging and firm performance (see Bartram et al ., ; Haushalter et al ., ; Pérez‐González and Yun, ). More recently, Chen, Han and Zeng () also provide robust evidence in support of the view that companies who use derivative hedging achieve higher returns than non‐users do.…”
Section: Managerial Implications Of Liq‐garch Modelmentioning
confidence: 83%
“…Several studies have shown that there exists a positive relationship between derivatives hedging and firm performance (see Allayannis et al ., ; Bartram, Brown and Conrad, ; Haushalter et al ., ; Pérez‐González and Yun, ). More recently, Lau () has shown that hedging can strengthen company's ROA and ROE, while Chen, Han and Zeng () find that hedging companies announce higher returns than non‐users. Typically, hedging strategies are supported by a variety of econometric models aiming at forecasting the volatility of commodity prices.…”
Section: Financial Hedging and Business Performance: A Reviewmentioning
confidence: 99%
“…Next, the phase of interim is described as the phase among the date of the announcement and completion of the transaction. Lastly, the post-acquisition phase is described as the phase after the completion of the transaction, that could be also split into the integration phase and the post-integration phase (Ahern & Sosyura, 2014;Chen, Han & Zeng, 2017). Pre-acquisition phase includes the evaluation of the financial risk of the target firms.…”
Section: Pre-acquisition Phase Interim Phasementioning
confidence: 99%
“…Cross-border M&As involve extra risk components as a result of changes in culture, natural features, capital market growth, accounting instructions, and rules among the acquirer and the target firms contrasted to domestic M&As. More prominently, taking over by a foreign acquirer firm considerably changes the target firm's financial risk exposure (Chen, Han & Zeng, 2017). The different stages of the transaction of a standard M&A procedure and the related risks that Chen, Han & Zeng (2017) recommend are illustrated in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation